INISIATIF MSP (MALACCA STRAITS PATROLS) DALAM MENANGANI ANCAMAN PEROMPAK DI SELAT MALAKA - Julaene Foela Putri; M.Saeri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The Malacca Straits is defined as the world’s most significant international maritime choke-points, and considered as straits used or international navigation, especially for international shipping who conduct oil transportation, threatened in Malacca Straits would be very detrimental to the global economy. Report issued by the International Maritime Bureau (IMB) related to piracy and armed robbery against ships obviously cause anxious by the international. The great cooperation among three three state (Indonesia, Malaysia, Singapore) become emergency to handle this problem. The focus of this research is the MSP (Malacca Straits Patrols) initiative who build by three states specifically to solve the piracy and armed robbery in Malacca Straits. The MSP Initiative structured by three elements patrols, there is MSSP (Malacca Sea Straits Patrols), EiS (Eyes in the Sky), and IEG (Intelligence Exchange Group). This research uses International Cooperation theory which has been revealed by K.J Holsti. This research is qualitative research which is used by library observation. The result of this research prove that full commitment between Indonesia, Malaysia, Singapore, Thailand in MSP Initiative very effective to reduce the frequencies of piracy and armed robbery until it reaches zero level on 2014. The MSP Initiative also open wide the cooperation among big countries such US, Japan, India to strengthening the patrols in Malacca Straits.Keywords: MSP Initiatives, Malacca Straits Patrols, Piracy, Armed Robbery.